(E)-(4-Bromobenzylidene)amino cyclopropanecarboxylate - Liu, Xing-Hai (International Union of Crystallography, 2012)
In the title compound, C(11)H(10)BrNO(2), the dihedral angle between the benzene and cyclopropane ring planes is 49.4 (3)°. The C—C—N—O torsion angle is −175.1 (3)°, which indicates that the C=N double bond is in the E configuration.